The Influence of Service Quality, Product Quality and Personal Branding on Asset Purchase Decisions at PT Boll Putra Mario Parepare City - Firman; Wulan Pratiwi; Hasdiana; Abdul Azis (IECON: International Economics and Business Conference, 2024)
This study examines the influence of service quality, product quality, and personal branding on asset purchase decisions at PT Boll Putra Mario, Parepare City. The research employs observation and questionnaires as data collection methods, involving a sample of 109 respondents, all of whom have occupied homes provided by PT Boll Putra Mario. Data analysis includes multiple linear regression, hypothesis testing, determination tests, and t-tests, with data processed using SPSS version 20.0 software. The findings reveal that service quality, product quality, and personal branding significantly and positively impact asset purchase decisions. This indicates that higher service standards, superior product offerings, and a strong personal branding strategy can enhance consumer interest in purchasing assets from the company. Service quality plays a crucial role in ensuring customer satisfaction and trust, while product quality addresses consumer needs and expectations. Personal branding, meanwhile, strengthens the company’s image and appeal, directly influencing customer decisions. These results highlight the importance of maintaining and improving service quality, offering competitive and reliable products, and fostering a strong, trustworthy brand image. By focusing on these factors, PT Boll Putra Mario can further optimize its market position and attract more potential buyers in the Parepare City area.